P4 6 Satellite Stomps- Harry’s Power - Devenport, Hannah K; Hanna, Caitlin J R; Malkin, Oliver W B; Bakrania, Roshni A (Physics Special Topics, 2023)
We investigate the use of Kinetic Flooring during the "Satellite Stomps" in a performance of Harry Styles' "Love on Tour" as a way to produce the energy to power the entire show. We found that Harry alone would produce 2.63x10\(^-4\) kWh, while the entire show would use 15200 kWh, meaning a total of 57.8 million fans would be required to produce enough energy for the entire show.